Drilling engineering : advanced applications and technology - Miska, Stefan; Mitchell, Robert F., 1946-; Ozbayoglu, Evren M. ([New York] : McGraw Hill Education, 2021)
'A guide for petroleum engineers covering the fundamentals through the latest advances in technology to drill both on and off shore wells as safely and economically as possible'--
Includes bibliographical references and index.
Keywords: Oil well drilling; Gas well drilling